The roles actors play in policy networks: Central positions in strongly institutionalized fields. (10th June 2021) - Ingold, Karin; Fischer, Manuel; Christopoulos, Dimitris
Abstract: Centralities are a widely studied phenomenon in network science. In policy networks, central actors are of interest because they are assumed to control information flows, to link opposing coalitions and to directly impact decision-making. First, we study what type of actor (e.g., state authorities or interest groups) is able to occupy central positions in the highly institutionalized context of policy networks. Second, we then ask whether bonding or bridging centralities prove to be more stable over time. Third, we investigate how these types of centrality influence actors' positions in a network over time. We therefore adopt a longitudinal perspective and run exponential random graph models, including lagged central network positions at t1 as the main independent variable for actors' activity and popularity at t2. Results confirm that very few actors are able to maintain central positions over time.